Cardiovascular risk and stress in employees of a higher education institution - Eugênio Barbosa de Melo Júnior; Jayne Ramos Araújo Moura; Sâmia Suély Leal Borges; Açucena Leal de Araújo; Jackson Júnior Vieira de Castro; Ana Roberta Vilarouca da Silva (Universidade Federal do Ceará, 2016)
Objective: to analyze the association between high levels of stress and the frequency of cardiovascular risk factors in employees of a higher education institution. Methods: this is a cross-sectional study with 201 employees of a university. A form containing socioeconomic data, the International Physical Activity Questionnaire (short version), the Alcohol Use Disorders Identification Test and the Work Stress Scale were used for data collection. Data analysis was performed using the probability ratio and One-way analysis of variance tests. Results: worrisome frequencies of cardiovascular risk factors were identified, in which sedentary lifestyle, excess weight, and increased abdominal circumference presented the most expressive indexes. Regarding the stressors evaluated, some of the employees had increased stress indexes, distributed between the medium and high levels. Conclusion: sedentary lifestyle, excess weight, and increased abdominal circumference presented expressive high indexes, without statistically significant associations with the level of stress.